2011
DOI: 10.1097/jpn.0b013e31821693b2
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety in the NICU

Abstract: Patient safety is a worldwide priority aimed at preventing medical errors before they cause death, harm, or injury. Medical errors impact 1 in 10 patients worldwide (WHO), and their implications may include death, permanent, or temporary harm, financial loss, and psychosocial harm to the patient and in some cases to the caregiver. The unique aspects and the complexity of the neonatal intensive (NICU) environment, in addition to the vulnerability of the neonatal population increase the risk for medical errors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Moreover, the study by Reyna et al [ 20 ] on nurses in a nonteaching medicine indicated that nurses felt there is a lack of “communication openness and nonpunitive response to errors” which is similar to findings of current study that revealed that dental assistants had low score in “communication openness and nonpunitive response to errors” dimension.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the study by Reyna et al [ 20 ] on nurses in a nonteaching medicine indicated that nurses felt there is a lack of “communication openness and nonpunitive response to errors” which is similar to findings of current study that revealed that dental assistants had low score in “communication openness and nonpunitive response to errors” dimension.…”
Section: Discussionsupporting
confidence: 87%
“…[19] Finally, the study reveals that respondents strongly agreed on the criteria mentioned to evaluate the effectiveness of the courses and trainings listed in Table 2. As mentioned, medical errors impact 1 in 10 patients worldwide; [20] and consequently medication errors are due to wrong patient, wrong or delayed diagnosis and administration or method used for treatment and most common types of medication errors are those of dosing, prescribing, frequency and route of administration. Furthermore, it was also cited that wrong drug infusion rate via pumps, packaging/labelling of drugs, excess oxygen therapy, human factors, miscommunication and equipment/delivery devices failures, patient misidentification and false documentation were all identified as causes of medication errors.…”
Section: Nursing Training On Communicable and Emerging Infectiousmentioning
confidence: 99%
“…In the neonatal intensive care unit (NICU), the neonates are considered one of the most susceptible group, to medication errors that can lead to overwhelming, life-threatening significance [1].…”
Section: Introductionmentioning
confidence: 99%